2010
DOI: 10.2105/ajph.2008.151415
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Food Prices on Consumption: A Systematic Review of Research on the Price Elasticity of Demand for Food

Abstract: In light of proposals to improve diets by shifting food prices, it is important to understand how price changes affect demand for various foods. We reviewed 160 studies on the price elasticity of demand for major food categories to assess mean elasticities by food category and variations in estimates by study design. Price elasticities for foods and nonalcoholic beverages ranged from 0.27 to 0.81 (absolute values), with food away from home, soft drinks, juice, and meats being most responsive to price changes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
622
7
18

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 872 publications
(697 citation statements)
references
References 27 publications
50
622
7
18
Order By: Relevance
“…The research of Andreyeva et al (39) and Green et al (40) showed that the price of meat can effectively influence consumption. Therefore, the efficient measure of price control could be considered to adjust the consumption structure of meat in China.…”
Section: Resultsmentioning
confidence: 99%
“…The research of Andreyeva et al (39) and Green et al (40) showed that the price of meat can effectively influence consumption. Therefore, the efficient measure of price control could be considered to adjust the consumption structure of meat in China.…”
Section: Resultsmentioning
confidence: 99%
“…Our study extends the number of foods that are explicitly modeled in the simulation and in particular allows for a disaggregation of milk and cream into categories which have di ering levels of saturated fat. The importance of doing this is noted by (Andreyeva et al;2010) given the importance of milk as a source of saturated fat and the potential for reducing intakes by encouraging substitution between milk of di ering fat contents. In a similar vein we also estimate separate elasticities for fresh potatoes, crisps and chips because of the implications of consuming each of these potato based foods for health.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, price has varying effects on purchasing behaviour for different foods and beverages, depending on their specific price elasticities (48) . Finally, even with all other factors supporting the healthier food choice, access to healthy foods may be limited (44) .…”
Section: Discussionmentioning
confidence: 99%